Reframing Halal Standards as Operational Capability Bundles for Sustainable Production Performance in Micro Foodservice Enterprises - Choirun, Annisa'u; Astuti, Retno; Sucipto, Sucipto (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2025)
AbstractHalal integrity in micro-food businesses is not simply understood as ingredient compliance, but rather as consistent process control that impacts quality, food safety, efficiency, and production sustainability. Previous studies have focused largely on manufacturing and supply chains, resulting in limited empirical evidence on the role of halal operational standards in micro-food businesses. This study aims to analyze the influence of halal operational standards on sustainable production and identify the operational domains that most influence performance variation in A1 category food businesses. A cross-sectional survey was conducted at 15 active businesses in Malang City, East Java Province, Indonesia, with 45 respondents consisting of owners, chefs, and employees. Data were obtained through structured questionnaires, interviews, and field observations and then analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that the model has very strong explanatory power and predictive relevance, reflected in an R² value of 0.911 and a Q² of 0.829. Five domains had a positive and significant influence on sustainable production: management quality, facility location and building design, hygiene, sanitation, and food safety, halal logistics, and packaging and labeling. Halal food processing remained positive, but not statistically significant. These findings suggest that halal operational standards are better understood as complementary, multidimensional operational capabilities. Practical implications lie in strengthening governance, facilities, material logistics, sanitation, and clarity of product information.Keywords: Micro-catering, operational capabilities, halal food, sustainable production, halal operational standards AbstrakIntegritas halal pada usaha jasa boga mikro tidak cukup dipahami sebagai kepatuhan bahan, tetapi sebagai konsistensi pengendalian proses yang memengaruhi mutu, keamanan pangan, efisiensi, dan keberlanjutan produksi. Kajian sebelumnya masih banyak berfokus pada manufaktur dan rantai pasok sehingga bukti empiris tentang peran standar operasional halal pada jasa boga mikro masih terbatas. Penelitian ini bertujuan menganalisis pengaruh standar operasional halal terhadap produksi berkelanjutan dan mengidentifikasi domain operasional yang paling menentukan variasi kinerja pada usaha jasa boga golongan A1. Cross-section survey dilakukan pada 15 unit usaha aktif di Kota Malang, Provinsi Jawa Timur, Indonesia dengan 45 responden yang terdiri atas pemilik, koki, dan pegawai. Data diperoleh melalui kuesioner terstruktur, wawancara, dan observasi lapangan lalu dianalisis menggunakan Partial Least Square-Structural Equation Modelling (PLS-SEM). Hasil penelitian menunjukkan bahwa model memiliki daya jelas dan relevansi prediktif yang sangat kuat, tercermin pada nilai R² sebesar 0,911 dan Q² sebesar 0,829. Lima domain berpengaruh positif dan signifikan terhadap produksi berkelanjutan, yaitu kualitas manajemen, tempat usaha dan desain bangunan, kebersihan, sanitasi, dan keamanan pangan, logistik halal, dan kemasan dan label. Pengolahan pangan halal tetap berarah positif, tetapi tidak signifikan secara statistik. Temuan ini memperlihatkan bahwa standar operasional halal lebih tepat dipahami sebagai kapabilitas operasional multidimensi yang saling melengkapi. Implikasi praktisnya terletak pada penguatan tata kelola, fasilitas, logistik bahan, sanitasi, dan kejelasan informasi produk.Kata Kunci: Jasa boga mikro, kapabilitas operasional, pangan halal, produksi berkelanjutan, standar operasional halal